Migrating an APTCA assembly to the .NET Framework 4. - Rousos, Mike (MSDN magazine)
In the Microsoft.NET Framework 4, the common language runtime (CLR) security model has undergone some substantial changes. One of these changes, the adoption of Level2 transparency (much like Silverlight's security model), is likely to impact authors of AllowPartiallyTrustedCallers (APTCA) libraries. The reason for the impact is that the underlying workings of APTCA have changed in CLR v4. The APTCA attribute retains the ability to make a fully trusted library available to partially trusted callers, but the details of how that happens are different, and some modifications to APTCA library code are likely necessary as a result.